Management of asymptomatic irreversible with single visit endodontic treatment: A case report - Nugroho, Juni J.; Lestari, Dwi P. (Journal of Case Reports in Dental Medicine, 2023)
Objective: This case report aims to describe the management of single-visit endodontic treatment in asymptomatic irreversible pulpitis case.Methods: A 25-year-old woman came to RSGMP Unhas with complaint of a cavity in the lower left back tooth, had felt pain Â± 2 weeks ago. Intraoral examination showed thermal test (+), percussion (-), palpation (-). The periapical radiograph shows a normal periapical and the root appears straight. The case diagnosis was asymptomatic irreversible pulpitis. Root canal were treated with single-visit endodontic treatment. The root canal was prepared using single length techniques and obturated with single cone techniques.Results: Patient showed no complaints of pain after treatment, the teeth continued to function properly and nothing disturbed the patient`s comfort especially when chewing.Conclusion: Endodontic single-visit treatment provides good and satisfactory results in asymptomatic cases of irreversible pulpitis.Â